2018
DOI: 10.1111/sjos.12352
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy in high‐dimensional linear models and its application to genomic selection

Abstract: Genomic selection is today a hot topic in genetics. It consists in predicting breeding values of selection candidates, using the large number of genetic markers now available owing to the recent progress in molecular biology. One of the most popular methods chosen by geneticists is ridge regression. We focus on some predictive aspects of ridge regression and present theoretical results regarding the accuracy criteria, that is, the correlation between predicted value and true value. We show the influence of sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…This accuracy expectation was the goal of the different formulas derived from the works of [15, 16]. Via estimation of the QTL locations and effects, the authors of [27] compared the expectation of the theoretical accuracy to these analytical formulas and found that the former performed better than the other formulas. The most important issue with the theoretical accuracy formula is the estimation of the causal-QTL locations and effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This accuracy expectation was the goal of the different formulas derived from the works of [15, 16]. Via estimation of the QTL locations and effects, the authors of [27] compared the expectation of the theoretical accuracy to these analytical formulas and found that the former performed better than the other formulas. The most important issue with the theoretical accuracy formula is the estimation of the causal-QTL locations and effects.…”
Section: Discussionmentioning
confidence: 99%
“…The most important issue with the theoretical accuracy formula is the estimation of the causal-QTL locations and effects. The authors of [27] compared different penalized regression methods and revealed that adaptive LASSO [32] performed the best. We also compared different methods by plugging them into the theoretical accuracy formula, but in contrast to [27], we did not use the penalized regression estimators of the QTL effects because they are known to be biased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations